2018
DOI: 10.19082/6208
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of vitamin D in preterm infants and its association with premature-related respiratory complications: a case-control study

Abstract: Background and aimPrematurity and related problems, especially respiratory distress, are one of the main challenges for neonatal medicine. The aim of this study was to compare vitamin D levels in preterm infants with, and those without respiratory distress.MethodsThis case-control study was conducted in Ghaem and Emam Reza Hospitals in Mashhad (Iran) from 2015 to 2016. In this study, we examined 160 preterm infants weighing less than 2000 grams and born at less than 34 weeks’ gestation. Serum vitamin D levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
(49 reference statements)
0
30
0
Order By: Relevance
“…In a study by Choi et al, there was a significant relationship between infants born in the second trimester of pregnancy and severe vitamin D deficiencies compared to third-trimester neonates (26). Studies have shown that most vitamin D from the mother reaches the neonate in the last weeks of pregnancy (13).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In a study by Choi et al, there was a significant relationship between infants born in the second trimester of pregnancy and severe vitamin D deficiencies compared to third-trimester neonates (26). Studies have shown that most vitamin D from the mother reaches the neonate in the last weeks of pregnancy (13).…”
Section: Discussionmentioning
confidence: 98%
“…Although the main cause of this association was not determined, several studies have shown the role of vitamin D in other problems of premature newborns. Boskabadi et al found that vitamin D levels were lower in preterm infants with respiratory problems (13). Because respiratory problems are one of the most common causes of hospitalization of premature newborns and their mortality, vitamin D deficiency may be effective in increasing the risk of death in premature newborns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations